Industrial policy in the conditions of neoindustrialization: approaches to formation - V. V. Biryukov; V. P. Ploskonosova (Вестник СибАДИ)
Alternative concepts, variously interpreting reasons of interference of the state in economy and also currently occurring changes in carrying out industrial policy in developed and dynamically developing countries are shown in the article. There are considered problems of changing priorities of industrial policy in the conditions of forming new paradigm of industrial development of the Russian economy and implementation of the organizational and economic changes providing overcoming of technological gap from the advanced industrial countries on the basis of using advantages of the catching-up economy.